2007
DOI: 10.1063/1.2434011
|View full text |Cite
|
Sign up to set email alerts
|

Role of the gold film nanostructure on the nanomechanical response of microcantilever sensors

Abstract: In this study, we have determined the relationship between the nanostructure of the gold film deposited on microcantilevers and the sensitivity and reproducibility of their static response to molecular adsorption. In order to tune the properties of the gold film, gold was deposited at different rates and thicknesses. The cantilever response to molecular adsorption was characterized by exposure of the cantilevers to mercaptohexanol in water. The morphology of the gold surface was characterized by atomic force m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…The experimental work carried out during the last decade on DNA SAMs on microcantilever surfaces has revealed that the mechanical signatures of SAMs of single and double stranded DNA (ssDNA and dsDNA) strongly depend on the immobilization protocols used, 11,12 the gold nanostructure 13,14 and even the electrostatic forces during immobilization. 15,16 Recent theoretical and experimental work has highlighted the fact that even slightly different experimental conditions, such as ionic strength, temperature or pH variations during immobilization, may lead to largely divergent mechanical effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental work carried out during the last decade on DNA SAMs on microcantilever surfaces has revealed that the mechanical signatures of SAMs of single and double stranded DNA (ssDNA and dsDNA) strongly depend on the immobilization protocols used, 11,12 the gold nanostructure 13,14 and even the electrostatic forces during immobilization. 15,16 Recent theoretical and experimental work has highlighted the fact that even slightly different experimental conditions, such as ionic strength, temperature or pH variations during immobilization, may lead to largely divergent mechanical effects.…”
Section: Introductionmentioning
confidence: 99%
“…19,24 For such purpose, sophisticated nanografting methods need to be applied. 25,26 Alternatively, the gold layer needs to comply with very restrictive conditions regarding surface roughness 13 and surface electrostatics, 16 while long incubation times are also applied, 24 which bans the use of technologies for high multiplexing, such as ink-jet low volume dispensing. 3,10 In this work we study the effect of relative humidity (RH) changes in ssDNA and dsDNA SAMs on gold.…”
Section: Introductionmentioning
confidence: 99%
“…Their domains have to be aligned close to one direction by applying an electric field on the films in order to exhibit a net piezoelectric effect. Consequently, the polarization vector can be reoriented along different directions, allowing polycrystalline PZT films to utilize either or modes [31,32]. In contrary, the polarization direction of the ZnO and AlN [33] or epitaxial PZT thin films is fixed by the crystal structure, and thus reorientation to other directions is not possible.…”
Section: Piezoelectric Mems Structures and Operation Modesmentioning
confidence: 99%
“…Additionally, it is also used for the device design optimization, in order to find the optimal parameters. Many previous researches have developed analytical power models describing the effect of the parameters on the generated output power of the piezoelectric energy harvesters [31][32][33][34][35][36][37][38]. In this work, the analytical power model for a piezoelectric bimorph cantilever with a mass placed on the free end developed by Roundy et al is applied [12].…”
Section: Analytical Power Model For Piezoelectric Energy Harvestersmentioning
confidence: 99%
“…As outcome of previous investigations, 16,22,23 it is known that the adequate performance of the DNA biomechanical sensors requires the coverage of the cantilever surface by a thick enough gold layer of about 20 nm. In order to ensure that the gold layer grown by PLD meets this requirement, gold deposition was carried out using 144 000 laser pulses (Table I).…”
Section: A Fabrication and Characterization Of Coated Substratesmentioning
confidence: 99%